XANES and luminescence studies of M2O3-CaO-SiO2-B2O3 (M2O3 = Y2O3 and La2O3) glasses doped with Dy3+ ions - Siriprapa Kaewjaeng (2018)
© 2018 Trans Tech Publications, Switzerland. The Dy3+-doped glasses of the M2O3: CaO: SiO2:B2O3 (M2O3 = Y2O3 and La2O3) materials have been successfully fabricated with the 0.5 % mol of the Dy2O3 concentration, and thoroughly investigated based on the physical, optical, photo- and radioluminescence properties. The developed glass materials were prepared from the compositions of 25M2O3: 10CaO: 10SiO2: (55-x)B2O3: 0.5Dy2O3 by the conventional melt-quenching technique at 1, 400°C. The clear sample of the doped La2O3 glass demonstrated higher density and the molar volume than those of the doped Y2O3 glass. From the spectrophotometry, the absorption peaks of the Dy3+ ions were clearly observed in both glasses. The photoluminescence (PL) spectra of the developed glasses indicated two-colors with two strongest peaks at 577 nm (4F9/2→6H13/2) and 482 nm (4F9/2→6H15/2). In addition, the emission spectra from the radioluminescence (RL) were identical to those from the PL measurements. From the results of the PL and RL measurements, the Y2O3 glass had higher emission in the intensity than the La2O3 glass. The X-ray absorption near edge spectroscopy (XANES) with the synchrotron radiation was carried out in fluorescent-yield mode to determine the average oxidation number of the Dy ions dispersed in the glass matrices. The Dy L3-edge XANES spectra of both developed glasses were nearly identical with the sharp white line at 7795.5 eV and the edge energy of 7793 eV. Compared to the XANES spectrum of the pure Dy2O3 standard, both glasses showed the difference smaller than 0.5 eV, and therefore confirmed the oxidation number of the Dy ions of 3+.